2016
DOI: 10.1007/s10495-016-1309-3
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q10 protects renal proximal tubule cells against nicotine-induced apoptosis through induction of p66shc-dependent antioxidant responses

Abstract: Chronic nicotine exposure (via smoking, E-cigarettes) increases oxidative stress in the kidney that sensitizes it to additional injury in experimental models and in the renal patient. The pro-apoptotic p66 protein-via serine36 phosphorylation that facilitates its mitochondrial translocation and therein cytochrome c binding-generates oxidative stress that leads to injury of renal proximal tubule cells during chronic nicotine exposure. Coenzyme Q10-a clinically safe antioxidant-has been used against nicotine/smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…It is that the Ser36 phsophorylated p66shc does not translocate to the mitochondria -as during its prooxidant function -but rather activates the ARE and hence, a set of antioxidant genes that harbors the ARE in their promoter. This phenomenon has been described in erythroleukemia cells upon hemin treatment (25) and by us in renal proximal tubule cells upon coenzyme Q10 treatment (17). Some studies demonstrated that RES protects keratinocytes (26) and prostate cells (27) from injury via activating (Ser36 phosphorylating) p66shc.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…It is that the Ser36 phsophorylated p66shc does not translocate to the mitochondria -as during its prooxidant function -but rather activates the ARE and hence, a set of antioxidant genes that harbors the ARE in their promoter. This phenomenon has been described in erythroleukemia cells upon hemin treatment (25) and by us in renal proximal tubule cells upon coenzyme Q10 treatment (17). Some studies demonstrated that RES protects keratinocytes (26) and prostate cells (27) from injury via activating (Ser36 phosphorylating) p66shc.…”
Section: Discussionmentioning
confidence: 56%
“…To prevent Serine36 phosphorylation or mitochondrial cytochrome c binding of p66shc, cells were transfected with a Serine-36 phosphorylation-deficient mutant p66shc (S36A) or a cytochrome c-binding-deficient mutant p66shc (W134F) as described elsewhere (16). Nrf2 expression was knocked down by a Nrf2 siRNA (Santa Cruz, Ja Jolla, CA) using Lipofectamine 3000 (Life Technologies, Grand Island, NY, USA) as previously described (17). HO-1 expression was knocked down by an HO-1 siRNA (Santa Cruz, La Jolla, CA) using Lipofectamine 3000 (Life Technologies, Grand Island, NY, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Cells were transfected with either of the following reporter luciferase plasmids: HO1 promoter (20); CRE, ELK1 (Agilent Technologies, Santa Clara, CA) or MnSOD promoter (21). Cells were also co-transfected with a renilla luciferase plasmid (Promega, Madison, WI, USA) using Lipofectamine 3000 as suggested by the manufacturer (Thermo Fisher Scientific) and described elsewhere (19). After treatment, as described above, firefly and renilla luciferase activities were determined by a Dual Luciferase assay kit (Promega) and calculated as firefly/renilla ratios and expressed as a percentage that of the control.…”
Section: Methodsmentioning
confidence: 99%
“…Plasmid transfection. Some cells were also transfected with a shorthairpin p66shc (shp66shc) (19) to knockdown p66shc expression or with a plasmid containing constitutively activated CREB (VP16CREB) (22) in order to overexpress CREB.…”
Section: Methodsmentioning
confidence: 99%
“…Nrf2 expression was knocked down by a Nrf2 siRNA (Santa Cruz, Ja Jolla, CA) using Lipofectamine 3000 (Life Technologies, Grand Island, NY) as we reported earlier [23]. To knockdown MnSOD expression, NRK52E cells were transfected with a short-hairpin (sh)MnSOD plasmid (Addgene, Cambridge, MA, USA) using Lipofectamine 3000 as we described elsewhere [24].…”
Section: Methodsmentioning
confidence: 99%